A cross‐sectional study of the interaction between night shift frequency and age on hypertension prevalence among female nurses. Issue 5 (14th March 2022) - Zhao, Bin; Li, Jing; Li, Yun; Liu, Jie; Feng, Di; Hao, Yuming; Zhen, Yanjie; Hao, Xiaoran; Xu, Menghui; Chen, Ximin; Yang, Xiulan; Zuo, Aifang; et al.
Abstract: Night shift is a common work schedule. This study aimed to analyze the interaction between age and frequency of night shift on the hypertension prevalence. A census questionnaire was conducted in 512 medical institutions in 11 cities of Hebei Province. One lakh twenty‐one thousand nine hundred three female nurses were included in this study. Binary Logistic regression analysis was done by SPSS Version 26.0. The youngest age group without night shift was used as the reference group. The odds ratio was calculated by different combinations of interaction items. Interaction coefficients were calculated by an Excel table designed by Andersson. Compared with the 18–25 year old ones without night shift, there existed an additive interaction between the age of 36–45 and more than 5–10 night shifts per month on hypertension prevalence. Odds ratio, the relative excess risk of interaction, the attributable proportion of interaction, and the synergy index and their 95% confidence intervals were 2.923(2.292‐3.727), 0.631(0.309‐0.954), 0.216(0.109‐0.323), 1.488(1.158‐1.913). Additive interaction was also found between the age of 36–45 and more than 10 night shifts per month. OR, RERI, API, SI, and their 95% confidence intervals were 3.430(2.273‐5.175) 1.037(0.061‐2.013), 0.303(0.089‐0.516), and 1.746(1.093‐2.788). There also existed an additive interaction between the age of 46–65 and more than 5–10 night shifts per month on hypertension prevalence. OR, RERI, API, SI, and their 95% confidence intervals were 7.398(5.595‐9.781) 1.809(0.880‐2.739), 0.245(0.148‐0.341), and 1.394(1.199‐1.622).There existed interaction between specific age groups and night shift frequency on the prevalence of hypertension among female nurses.